Scrutinizing Local Probiotic Supplements and Drinks Available in the Bangladesh Market - Akter Fatema; Karmaker Pranab; Nusrat Chowdhury Nafisa; Nur Showva Nazmir; Ahmed Zabed Bin; Rabby Md. Raisul Islam; Razu Mamudul Hasan; Hossain Md. Iqbal; Khan Mala (International Journal of Nutrition, 2024)
The host's health may benefit from the probiotic microorganisms found in many products available on the market. In addition to food, these products include dietary supplements, food for special medical purposes, medicines, cosmetics, and medical devices. These products have anywhere from one to a dozen strains of bacteria from the same or different species, and sometimes they also have strains of fungi. Since the health benefits of probiotics depend on the strain, the number of cells in a dose, and the absence of pathogenic microorganisms, it is crucial to regulate the quality of probiotics. Depending on how a product is classified, how it looks, and how many microorganisms it has, it is very important to count and identify the microorganisms correctly. We investigated nine probiotic products in this study: five commercially available probiotic supplements and four probiotic drinks. The majority of commercial products did not contain all of the labeled lactic acid bacteria, nor did they contain any possibly harmful microorganisms. To ensure that consumers in Bangladesh obtain good products, probiotic-containing product rules and regulations should be developed. Furthermore, it should be the duty of probiotics-containing product manufacturers to provide consumers with information that is accurate, reliable, and compliant with legal and scientific requirements
Keywords: Probiotic drinks